NGS Analysis of Clonality and Minimal Residual Disease in a Patient with Concurrent Richter’s Transformation and CLL/SLL - Shrihari S. Kadkol; Joshua Bland; Ashley Kavanaugh; Hongyu Ni; Vijeyaluxmi Nehru; David Peace (Case Reports in Hematology)
B-cell lymphomas are neoplastic proliferations of clonal B lymphocytes. Clonality is generally determined by PCR amplification of VDJ rearrangements in the IgH heavy chain or VJ rearrangements in Igκ/Igλ light chain genes followed by capillary electrophoresis. More recently, next-generation sequencing (NGS) has been used to detect clonality in B-cell lymphomas because of the exponential amount of information that is obtained beyond just detecting a clonal population. The additional information obtained is useful for diagnostic confirmation, prognosis assessment, and response to therapy. In this study, we utilized NGS analysis to characterize two histologically distinct lymphomas (DLBCL and CLL/SLL) that were detected contemporaneously in an asymptomatic patient. NGS analysis showed that the same VDJ rearrangement was present in nodal (DLBCL) and marrow (CLL/SLL) biopsies confirming that the DLBCL resulted from Richter’s transformation of a subclinical CLL/SLL. The V region of the rearrangement remained unmutated without somatic hypermutation. In silico analysis showed that the HCDR3 sequence was heterogeneous and not stereotypic. Minimal residual disease analysis by NGS showed that the tumor clone decreased by 2.84 logs in the bone marrow after R-CHOP therapy. However, a small number of tumor cells were still detected in the peripheral blood after R-CHOP therapy. Subsequent allogeneic transplantation was successful in eradicating the tumor clone and achieving deep molecular remission. We show that NGS analysis facilitated clinical management in our patient by helping to characterize the VDJ rearrangement in detail and by tracking minimal residual disease with high sensitivity and specificity.